2009
DOI: 10.1199/tab.0121
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate-Derived Amino Acid Biosynthesis inArabidopsis thaliana

Abstract: The aspartate-derived amino acid pathway in plants leads to the biosynthesis of lysine, methionine, threonine, and isoleucine. These four amino acids are essential in the diets of humans and other animals, but are present in growthlimiting quantities in some of the world's major food crops. Genetic and biochemical approaches have been used for the functional analysis of almost all Arabidopsis thaliana enzymes involved in aspartate-derived amino acid biosynthesis. The branch-point enzymes aspartate kinase, dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 145 publications
1
85
0
Order By: Relevance
“…Cell wall preparation and lignin quantification were performed following the method described by Lange et al (1995). Briefly, tubes containing about 200 mg of frozen samples were treated with 1 mL of methanol, shaken for 1 h, and then centrifuged at 7,500g for 5 min.…”
Section: Lignin Staining and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell wall preparation and lignin quantification were performed following the method described by Lange et al (1995). Briefly, tubes containing about 200 mg of frozen samples were treated with 1 mL of methanol, shaken for 1 h, and then centrifuged at 7,500g for 5 min.…”
Section: Lignin Staining and Quantificationmentioning
confidence: 99%
“…ALS, Acetolactate synthase; AS, Asn synthetase; ASN, asparaginase; BCAT, branched-chain aminotransferase; CBL, cystathionine b-lyase; CGS, cystathionine g-synthase; DAP-D, diaminopimelate decarboxylase; DAP-F, diaminopimelate epimerase; DHAD, dihydroxy acid dehydratase; DHDPR, dihydrodipicolinate reductase; DHDPS, dihydrodipicolinate synthase; HSDH, homoserine dehydrogenase; HSK, homoserine kinase; KARI, ketol-acid reductoisomerase; MS, Met synthase; TD, Thr deaminase; TS, Thr synthase. main pathways: (1) the biosynthesis of Asn in the cytosol (Lea and Azevedo, 2003;Lea et al, 2007); and (2) the biosynthesis of Lys, Met, Thr, and Ile through the socalled Asp metabolic pathway in the plastids (Azevedo et al, 2006;Jander and Joshi, 2009;Galili, 2011;Fig. 1).…”
mentioning
confidence: 99%
“…In major field crops, such as corn (Zea mays), rice (Oryza sativa), soybean (Glycine max), and potato (Solanum tuberosum), Asp-derived amino acids Lys, Met, Thr, and Ile are present at levels that limit the nutritional values (Müntz et al, 1998;Debabov, 2003;Pfefferle et al, 2003;Stiller et al, 2007). Increasing the contents of these amino acids in crop plants has long been a major goal of traditional breeding and genetic engineering Ufaz and Galili, 2008;Jander and Joshi, 2009). Genetic improvement requires a better understanding of the pathways and regulation of Asp-derived amino acids.…”
mentioning
confidence: 99%
“…For example, the Arabidopsis (Arabidopsis thaliana) nuclear genome contains three AKencoding genes (AK1 [At5g13280], AK2 [A5g14060], and AK3 [At3g02020]) and two AK-HSDH-encoding genes (AK-HSDH1 [At1g31230] and AK-HSDH2 [At4g19710]; Jander and Joshi, 2009). Public microarray data indicated that the five enzymes are expressed in all plant tissues (Schmid et al, 2005;Winter et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation